The Qur’anic exegesis, reformism, and women In twentieth century Indonesia - Ismail, Norbani (Center for the Study of Islam and Society (PPIM), Syarif Hidayatullah State Islamic University of Jakarta, 2017)
The paper examines the process of idea formation and intellectual roots of al-Manār reform in the field of tafsīr and the transmission of its ideas through the tafsīr work of Haji Abdul Malik Karim Amrullah, also known as Hamka (d. 1981). It argues that Hamka internalized al-Manār reform in his writings, particularly in his seminal exegetical work, Tafsir al-Azhar. This paper studies Hamka’s interpretation of the Qur’anic verses and passages related to women, such as: equality in marriage and divorce, gender equality, polygamy, and modesty. Hamka exhibited originality and creativity within a Southeast Asian context in interpreting these verses related to women’s issues. His writing also synthesized and manifested the symbiotic links between past exegetical approaches and modern ones. The result was an interpretation of the Quran that speaks to the Southeast Asian indigenous Muslim culture, while being firmly rooted within the Islamic intellectual tradition and modernist reform.